Experimental study of a suspended subsea module at different positions in the splash zone. (May 2021) - Zan, Yingfei; Guo, Ruinan; Yuan, Lihao; Ma, Qingwei; Zhou, Ao; Wu, Zhaohui
Abstract: During the lifting of submerged marine modules, the highest dynamic loads occur in the splash zone. These forces are highly dynamic and cannot easily be estimated with sufficient accuracy using simple calculations or high-fidelity computational fluid dynamics because of their irregular and complex geometries. We conducted an experimental study in a wave tank to investigate the dynamics of a large subsea module in the splash zone subject to irregular waves. The experiments were conducted using a 1:8 scale model of a subsea module, similar to that designed by Offshore Oil Engineering Co., Ltd., for the subsea pipeline from the Wenchang gas fields to the Yacheng pipeline. The model was examined at five different positions relative to the free surface, from completely above the surface to fully submerged. The resulting data are analyzed in the time and frequency domains. Spectral analysis and a dynamic effect parameter are used to analyze the dynamic loads on the subsea module. Several time-domain numerical analyses are performed with different peak periods, and the tension of the sub-slings is obtained. The experimental results for the relative forces and motions of the subsea module are presented, providing a reference for the design of other similar modules and their installation and validation data for computational modeling. Highlights: Experiments performed to analyze a large suspended subsea module in the splash zone. Subsea module tested at five elevations, from above the surface to fully submerged. Effects of irregular waves on the structure were measured and analyzed. Time-domain and spectral analyses of relative forces and motions conducted. Dynamic effects used to analyze the dynamic tension on the subsea module.